Pedicularis multicolor (Orobanchaceae), a new replacement name for the Pedicularis inconspicua - Li, Wenjun; Guan, Kaiyun; Abduraimov, Ozodbek; Feng, Ying (Phytotaxa, 2020)
Pedicularis inconspicua Vved (18 June, 1955: 811) was originally described as a new species from Uzbekistan and six years later considered as endemic for this country (1961:492). As part of the ongoing work for the preparation the checklist of vascular plant of Central Asia, we realized that the name P. inconspicua is an illegitimate later homonym of P. inconspicua Tsoong (18 January, 1955: 292), according to the Art. 53.1 of the International Code of Nomenclature for algae, fungi, and plants (ICN) (Turland et al. 2018).